2018
DOI: 10.3892/ijo.2018.4589
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of copy number alterations in primary breast tumors of South African patients and their impact on functional cellular pathways

Abstract: Breast cancer is the most common and the leading cause of female mortality among South African (SA) women. Several non-biological and biological risk factors may be attributed to their observed high mortality rate; however, the molecular profiles associated with their breast tumors are poorly characterized. The present study examined the patterns of genome-wide copy number alterations (CNAs) and their potential impact on functional cellular pathways targeted by cancer driver genes in patients with breast cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 57 publications
1
5
0
Order By: Relevance
“…In the Tunisian population, Shan et al ( 154 ) and Hamdi et al ( 152 ) identified rs1219648, rs2981582, rs8051542, rs889312, and rs889312 as breast cancer susceptibility single nucleotide polymorphisms (SNPs), with rs9911630 as the SNP with the strongest effect on the expression of BRCA1 and two long non-coding RNAs (NBR2 and LINC008854). The genome-wide copy number alteration analysis of breast cancer in South African women ( 153 ) identified the amplification in Xp22.3 and 6p21-p25, and other regions that affect known cancer genes like CCND1 , CDKN1A , MDM2 , TP53 , and SMAD2 . Meanwhile, the whole-exome sequencing study by Hamdi et al ( 152 ) and Riahi et al ( 156 ) linked breast cancer in Tunisian women to alterations in MMS19 , DNAH3 , POLK , KATβ6 , and RCC1 in BRCA1/2 mutation-negative patients with familial breast cancer.…”
Section: Resultsmentioning
confidence: 99%
“…In the Tunisian population, Shan et al ( 154 ) and Hamdi et al ( 152 ) identified rs1219648, rs2981582, rs8051542, rs889312, and rs889312 as breast cancer susceptibility single nucleotide polymorphisms (SNPs), with rs9911630 as the SNP with the strongest effect on the expression of BRCA1 and two long non-coding RNAs (NBR2 and LINC008854). The genome-wide copy number alteration analysis of breast cancer in South African women ( 153 ) identified the amplification in Xp22.3 and 6p21-p25, and other regions that affect known cancer genes like CCND1 , CDKN1A , MDM2 , TP53 , and SMAD2 . Meanwhile, the whole-exome sequencing study by Hamdi et al ( 152 ) and Riahi et al ( 156 ) linked breast cancer in Tunisian women to alterations in MMS19 , DNAH3 , POLK , KATβ6 , and RCC1 in BRCA1/2 mutation-negative patients with familial breast cancer.…”
Section: Resultsmentioning
confidence: 99%
“…The murine homologous band to human 19p13.1 is involved also in break events in all three studied cell lines, and this region was identified to comprise genes correlated for enhanced BC risk [ 29 , 31 , 47 ]. Furthermore, mutations in this region are strongly associated only with ER-negative BC subtypes [ 33 ]. Moreover, in TA3 Hauschka and C-127I, breakpoints homologous to human band 14q32 could be observed.…”
Section: Discussionmentioning
confidence: 99%
“…Imbalances and breakpoints being observed in JC were determined according to aCGH and mcb data, and aligned to human homologous regions using Ensembl and the UCSC Genome Browser, as previously described [19]. The obtained data were compared to genetic changes known from human BCs according to literature [7,[20][21][22][23][24][25][26][27][28][29][30][31][32].…”
Section: Discussionmentioning
confidence: 99%